Modeling Net Benefit Improvement Through Leadership Support: A Case Study on Free Nutritious Meals (MBG) - Maulana, Yono; Prasetyo, Dedi; Windayanti; Harisandi, Prasetyo (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
This study aims to propose and empirically test a model that explains how System Quality (QS), Training Effectiveness (EP), and System Usage (PS), under the influence of Leadership Support (DK), contribute to Net Benefits (MB) in the context of the Free Meal Program (MBG) in Indonesia. The methodology used is a case study with data collection through a survey of program implementers and stakeholders. The main analysis technique proposed is Structural Equation Modeling (SEM). The hypothetical findings show that Leadership Support significantly moderates the relationship between System Use and Net Benefits, and System Quality and Training Effectiveness have a positive effect on System Use. The main contribution of this research is the extension of the DeLone & McLean Information Systems Success Model by integrating a comprehensive leadership support construct in the context of a large-scale public welfare program. Practical implications are aimed at improving the effectiveness of MBG programs and similar public initiatives.